Stock exchanges of Baltic countries: Development and prospectives - Ginevičius, Romualdas; Tvaronavičiene, Manuela (Journal of Business Economics and Management, 2003)
The paper deals with Stock Exchanges of Lithuania, Latvia and Estonia. Authors tackle issues related with differences and peculiarities, activity and prospects of development of the Stock Exchanges. The main emphasis has been put on looking for the best solutions for effective functioning of Lihuanian Stock Exchange. Various variants of privatization have been considered.First Published Online: 14 Oct 2010